Developing child-friendly cities: Young children’s participation in urban planning - Terese Wilhelmsen; Steinar Øvreås; Hege Roll-Hansen; Anne-Line Bjerknes; Simen Thorrud (Journal of Childhood, Education & Society, 2023)
This article is based on a collaborative project between a municipality and a research team, aiming to investigate participatory methods that promote young children’s interest and participation in, and access to express their views in connection with, urban planning processes. The research question was: What characterizes a child-friendly city for young children and their families? The article is framed within the perspective of children’s rights, affordance and child-friendly outdoor environments. The project has employed multiple research methods. The participants were children (aged 3-6) and parents from three early childhood education and care institutions. The children (n=16) participated in guided tours, field conversations, drawing and constructive play using Lego. The parents (n=14) participated by identifying the locations that they preferred to frequent with their children, and a structured survey was used to identify what the parents liked and disliked about the places they identified. Our findings indicate that there are four important features that characterise a child-friendly city: 1) The availability of ‘green lungs’, 2) Creative and challenging play opportunities, 3) Places for the whole family, and 4) Safe playgrounds and walking routes. We discuss how better knowledge of what characterizes a child-friendly city can contribute to planning processes.